Qualificação e permanência do agricultor familiar no campo: a Casa Familiar Rural do município de Candói PR - Carmo, Raquel Mendes do (2010)
This work presents the relation between permanence in the field and the qualification of family farmers. In order to have this permanence and continuety in rural activity, the qualification allows, while social construction, an interaction between the elements involved, namely, the environment and people. Qualify means not only prepare them to cope with new technologies, but, educate them, teach them how to search for knowledge, in order to improve their action in activity and the environment in which they live. For the remaining it is needed the use of the qualification of the young farmer, to aggregate value to their activities, clearly and with the knowledge. An instrument for this knowledge occurs, is the Rural Family House (Casa familiar Rural) a helper in the decision to remain, the theoretical knowledge taught in addition to the practice helps the young farmer to learn accordingly to his own reality. In this way, to continue their activity, it is necessary, to learn and chase the activity diversification. For this learning becomes a qualification, the young farmer needs to be always constantly novitiate, that is, be looking for knowledge that promotes the activity and prepares for the work in rural property. With the qualification, the permanence becomes an activity able to bring benefits for the young farmers and also for their families, as well as enhances the family agriculture, therefore, the sector is responsible for food security in the country, that is, the basic food consumed by Brazilians. Denoting with it, the family farming shows a capacity of generation of income, and represents 75% of hand-to-work used in the field. Therefore, for this analysis, family farming, the permanence of the young farmer in the field and its relationship with the qualification, reflects the reality of the process.